Aplicación de la técnica LIBS en estudio del agua en el sendero “El Limón” del municipio de Palmar de Varela -Atlántico (2021)
In this work, the application of Laser Induced Plasma Spectroscopy (LIBS) is presented as a complementary method for the study and characterization of an underground water sample from the “El Limón” trail in the municipality of Palmar de Varela - Atlántico in Colombia. To carry out the study, the Geophysical electrical prospecting technique was first used, in order to identify underground aquifers in the study area, later the water samples were extracted and then analyzed using the LIBS technique. For the generation of the plasma-laser, a pulsed Nd: Yag laser was used with a length of 532 nm and a duration of ~ 5ns, the laser radiation on the sample was focused using a converging lens of 12 cm focal length, the energy per pulse was approximately 60 mJ, the relative humidity of the environment was 55% with a temperature of 24 ° C. The spectra of the laser plasma on the sample were recorded with an Echelle type spectrograph coupled to an ICCD camera within the spectral region of 200-950 nm. The spectral assignment of the lines found in the spectra of the sample was carried out, compared with the spectra taken from spectral sources known as: plasma-laser in Air and the NIST database, identifying the elements present Ca, N, Cl, O, F, and Na.